2021
DOI: 10.1097/ee9.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PM2.5 air pollution sources and cardiovascular health

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The conclusion that PM 2.5 is a causative risk factor for CVD is consistent with the previous studies with the populations in Asia [25,26], Europe [27,28], and USA [29,30]. The strengths of our study include a large sample size, investigation of CVD subtypes, and adjustment for and analysis of the effects of multiple confounding factors, including obesity, race, health care resources, household income, and variables directly linked to cardiovascular health, such as elderly age, smoking, high cholesterol prevalence, and blood pressure and cholesterol controlling medication nonadherence.…”
Section: Discussionsupporting
confidence: 91%
“…The conclusion that PM 2.5 is a causative risk factor for CVD is consistent with the previous studies with the populations in Asia [25,26], Europe [27,28], and USA [29,30]. The strengths of our study include a large sample size, investigation of CVD subtypes, and adjustment for and analysis of the effects of multiple confounding factors, including obesity, race, health care resources, household income, and variables directly linked to cardiovascular health, such as elderly age, smoking, high cholesterol prevalence, and blood pressure and cholesterol controlling medication nonadherence.…”
Section: Discussionsupporting
confidence: 91%
“…Nitrates, which, like sulfates, are components of PM 2.5 resulting from fossil fuel combustion sources that are acidic and can therefore engender similar potentiation of metals' solubility and bioavailability. Indeed, a recent analysis of cardiovascular mortality in the Catheterization Genetics (CATHGEN) cohort found that PM 2.5 from both ammonium bisulfate (pH = 1.42 at 0.1 M) and ammonium nitrate (pH = 5.22 at 0.1 M) were associated with increased prevalence of myocardial infarction per IQR exposure in the population (OR = 1.20; 95% CI = 1.10, 1.29, and OR = 1.35; 95% CI = 1.20, 1.53, respectively [144]).…”
Section: Role Of Metals In Oxidative Stress and Inflammationmentioning
confidence: 99%
“…More than 100 years ago, Russian academic specialists Anichkov and Ignatovskii were the first to show that lipid metabolism disorders are one of the key risk factors for the development of atherosclerosis and CVDs [ 67 ]. Although the dietary habits of people make the greatest contribution to the disturbance of lipid metabolism [ 67 ], some academic specialists have also traced the relationship between the effect of PM 2.5 fine particles and lipid metabolism disorders [ 68 - 70 ]. Thus, the randomized, double-blind study has shown that exposure to PM 2.5 causes significant changes in the concentrations of a number of metabolic parameters of blood serum, in particular, the lipid spectrum, amino acids, glucose and several hormonal parameters [ 70 ].…”
Section: Description Of Pm 25mentioning
confidence: 99%